Utilization of Tranexamic Acid for Recurrent Angioedema after ARB Discontinuation: A Case report and Review of the Literature - Sobash, Philip T.; Vedala, Krishna; Kamoga, Gilbert-Roy (Archives of Clinical and Medical Case Reports, 2021)
The incidence of ARB-induced angioedema is an insufficiently reported incidence in medical literature, due to its infrequent incidence and confusion with other confounding factors. Any time patients are on medications that involve the RAAS pathway, suspicion needs to be raised concerning their involvement in angioedema. Cessation of the offending agent is the only definitive way to prevent attacks. Although not well described in the literature, there are reports of recurrence of angioedema after cessation of individuals previously taking ARBs. This raises the question of whether in this transition period after removal can we prophylactically stop an attack?. We present the case of a 62-year-old female who was hospitalized for recurrent angioedema three times before it was decided to stop Olmesartan. During the third hospitalization, she was given tranexamic acid to aid in symptom management along with steroids and antihistamines. After discontinuation, she presented twice to the ER with similar symptoms. We discuss the need for surveillance of angioedema attacks after iatrogenic kinin-mediated angioedema along with the literature on tranexamic acid utilization during this latency period to help prophylactically reduce intermittent attacks.